Einige Bemerkungen zur Biologie von Pristiphora moesta (Zaddach, 1876) (Hymenoptera: Tenthredinidae). - Adam, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1963)
The above publication on the bionomy and phenology of the larval instars of Pristiphora moesta (Zaddach, 1876) is to present some dates mainly obtained under field conditions and additional notes on morphological characters of the egg and the larvae.